2018
DOI: 10.1063/1.5017683
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetoelectric effect in M-type hexaferrites by Co substitution into trigonal bi-pyramidal sites

Abstract: Article:Beevers, J. E., Love, C. J., Lazarov, V. K. orcid.org/0000-0002-4314-6865 et al. The magnetoelectric effect in M-type Ti-Co doped strontium hexaferrite has been studied using a combination of magnetometry and element specific soft X-ray spectroscopies. A large increase (> x30) in the magnetoelectric coefficient is found when Co 2+ enters the trigonal bi-pyramidal site. The 5-fold trigonal bi-pyramidal site has been shown to provide an unusual mechanism for electric polarization based on the displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…TS measurements have been carried out on Y type hexaferrites with composition Ba 0.5 Sr 1.5 Co 2 Fe 2 O 22 , (BSCFO) optimal to exhibit multiferroic properties [14,15]. In addition, Co substitution can enhance the magnetoelectronic effect in hexaferrites [16]. It is expected that the different spin configurations modify the magnetic properties detected with TS measurement, so that it can be a versatile tool to establish the different temperature regions in which the magnetoelectric effect occurs.…”
Section: Introductionmentioning
confidence: 99%
“…TS measurements have been carried out on Y type hexaferrites with composition Ba 0.5 Sr 1.5 Co 2 Fe 2 O 22 , (BSCFO) optimal to exhibit multiferroic properties [14,15]. In addition, Co substitution can enhance the magnetoelectronic effect in hexaferrites [16]. It is expected that the different spin configurations modify the magnetic properties detected with TS measurement, so that it can be a versatile tool to establish the different temperature regions in which the magnetoelectric effect occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we have used the same 10Dq parameter (=1.1 eV) for all octahedral sites (2a, 4 f 2 , 12k). In addition, we have modeled the tetrahedral sites(4 f 1 ) with 10Dq = −0.5 eV, and the bipyramidal one(2b) with 10Dq = 0.8 eV, D τ = −0.08 eV and D σ = 0.01 eV using literature values 22 . The Slater parameters were reduced to 72% of the Hartree Fock values following ref.…”
Section: Resultsmentioning
confidence: 99%
“…The Slater parameters were reduced to 72% of the Hartree Fock values following ref. 22 . The Gaussian broadening value used for each peak in the simulated spectrum was 0.09 eV, in order to match the experimental resolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was reported that the Co 2+ substitution in M-type and W-type hexaferrites raises the magnetic saturation and the coercivity [20,21]. In addition, the Co substitution can enhance the magnetoelectric effect in hexaferrites, as established by Beevers et al [20].…”
Section: Introductionmentioning
confidence: 98%